A novel "hot spring"-mimetic hydrogel with excellent angiogenic properties for chronic wound healing. (January 2021) - Sheng, Lili; Zhang, Zhaowenbin; Zhang, Yu; Wang, Endian; Ma, Bing; Xu, Qing; Ma, Lingling; Zhang, Meng; Pei, Ge; Chang, Jiang
Abstract: The treatment of chronic wounds is a major challenge in regenerative medicine, and angiogenesis is known to be critical for chronic wound healing. Hot springs with temperature in the range of 30–45 °C can promote blood circulation, and some hot spring elements including iron and silicon are also known to be active in promoting angiogenesis. Inspired by the hot spring function, we designed a novel bioactive photothermal hydrogel with "hot spring effect" based on fayalite (FA) and N, O-carboxymethyl chitosan (NOCS), which releases bioactive ions and has heating function to create hot ion environment in wound area. The hot spring-mimetic hydrogel showed significant enhancement of angiogenesis and chronic wound healing in vivo due to the in situ heating through photothermal effect combined with the bioactive ions (Fe 2+ and SiO4 4− ) released from the hydrogel. It is further confirmed that the synergetic effect of the mild heating and bioactive ions on angiogenesis was mainly because of the activation of different angiogenic factors and signaling pathways. Our study suggests that the hot spring-mimetic approach may be an effective strategy to design bioactive materials for promoting angiogenesis and tissue regeneration.